Clinical, histological and direct immunofluorescence features in oral mucosal patches striae diseases with malignant potential - Chun-lei Li; Xiao-meng Ren; Xin Fang; Hai-yan Luo; Hong Hua (Elsevier, 2023)
Background/purpose: Oral mucosal patches striae diseases (OMPSD) represent an important category of oral mucosal disease, most of which may have malignant potential (OMPSD-MP). The differential diagnosis is challenging due to overlap of their clinical and pathological features. Materials and methods: 116 OMPSD-MP patients were included in this cross-sectional study from November 2019 to February 2021, including oral lichen planus (OLP), oral lichenoid lesions (OLL), discoid lupus erythematosus (DLE), oral submucous fibrosis (OSF) and oral leukoplakia (OLK). The general information, clinical manifestation, histopathological and direct immunofluorescence (DIF) features were statistically analyzed and compared. Results: OLP was the major type of OMPSD-MP (64.7%), followed by OLL (25.0%), OLK (6.0%), DLE (2.6%) and OSF (1.7%), which were pooled as non-OLP group for further assessment. They shared many clinical and histological features in common. The rate of clinical-pathological diagnosis concordance was 73.5% for OLP, and 76.7% for total OMPSD-MP. DIF positive rate was significantly higher in OLP group than non-OLP group (76.0% vs. 41.5%, P < 0.001), in which the deposition of fibrinogen (Fib) and IgM were most frequently found. Conclusion: A significant overlap in clinical and histopathological features of OMPSD-MP was found, while DIF could be useful in differential diagnosis. Fib and IgM might be important immunopathological factors in OLP, which need further exploration.